Pemanfaatan Abu Sawit Dalam Produksi Telur Asin - Samsul Hadi; Setiawan, Deni; Nurlely, Nurlely; Kamelia, Suci; Putri, Lusiana Ernadi; Salma, Salma; Irawati, Irawati; Jannah, Raudatul (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Salted eggs are one of the most popular egg processing products in South Kalimantan. The purpose of making salted eggs is to remove the fishy taste and increase the shelf life of eggs. UKM Salted Egg 'Gold' Martapura is one of the salted egg producers in the region. Even though UKM 'Gold' Martapura Salted Egg already has a P-IRT permit, the permit has expired. Some of the problems faced by these SMEs include high ash prices, volatility in the base price of eggs, the lack of quality assurance for salted egg production, and product marketing management that is not yet optimal. The proposed solution is to increase sales profits by reducing production costs and improving the quality of the final product. In addition, it is necessary to increase insight into product innovation and the use of promotional media such as attractive label designs and unique marketing strategies. The results of implementing this solution show an increase in salted egg production, a decrease in production costs by utilizing palm ash which is available free of charge throughout the season, an increase in the overall quality and nutritional content of the product, and an increase in selling value through the renewal of salted egg packaging. Thus, it can be concluded that this program is very helpful for the development of the 'Golden' Salted Egg UKM business in the business they have run